PENGUJIAN KESETARAAN PRESISI DAN SKALA UKUR BUTIR-BUTIR PADA SKALA PSIKOLOGI - Wahyu Widhiarso (Universitas Gadjah Mada, 2012)
The purpose of this study is to identify the measurement models that appropriate to measure psychologicalattributes toward psychological scale. Measurement models that includes is parallel, tau-equivalent andcongeneric models. Each model has different assumptions according to each item’s precision and scalemeasuring on psychological scale. As a sample of psychological scale, this study uses Child DepressionInventory (CDI) and Rosenberg Self-Esteem Scale. Data was taken from the 3.183 adolescents from juniorand senior high school in DIY, with ages ranging from 15 to 19. Both scale were tested using the HotellingT2 test for testing the equality of mean and variance as well as confi rmatory factory analysis throughstructural equation modeling to rest the accuracy of the model. This study found that psychological scalestend to fi t better with the congeneric model than others. The congeneric model is one which assumesthat every item in a scale has a different precision and scale of measure. Therefore, it is concluded thatitems tend to be measured in psychological attributes, with relative variation.